2016
DOI: 10.1002/1873-3468.12518
|View full text |Cite
|
Sign up to set email alerts
|

A novel approach to assess the ubiquitin‐fold modifier 1‐system in cells

Abstract: The ubiquitin-fold modifier 1 (UFM1)-system, a ubiquitin-like protein conjugation system, is involved in the development of breast cancer and several hereditary neurological syndromes. However, the molecular mechanisms of UFM1-related pathogenesis remain unclear. Here, we show that in the absence of UFSP2, a deconjugating enzyme for UFM1, ectopic expression of both UFL1 and UFBP1, which serve as the E3-ligase complex for the UFM1-system, dramatically increases UFM1-conjugate formation at the endoplasmic reticu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 22 publications
5
33
0
Order By: Relevance
“…DDRGK1, the membrane anchor for the UFM1 E3 ligase complex, previously identified only following overexpression (5), was not identified in our UFMylome. Like the E3s for ubiquitin and other UBLs, DDRGK1 is subject to automodification by UFM1 when overexpressed (5,16). ASC1, a nuclear receptor coactivator reported to be a covalent UFMylation target (7), was also absent from our replicate datasets and has not been independently validated.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…DDRGK1, the membrane anchor for the UFM1 E3 ligase complex, previously identified only following overexpression (5), was not identified in our UFMylome. Like the E3s for ubiquitin and other UBLs, DDRGK1 is subject to automodification by UFM1 when overexpressed (5,16). ASC1, a nuclear receptor coactivator reported to be a covalent UFMylation target (7), was also absent from our replicate datasets and has not been independently validated.…”
Section: Discussionmentioning
confidence: 97%
“…The use of the C-terminally truncated UFM1 bypasses the need to remove the C-terminal SerCys dipeptide from pro-UFM1 to expose the reactive C-terminal Gly (Fig. 1A) (6,16). Immunoblot analysis conducted under reducing and nonreducing conditions confirmed that 6xHis-UFM1 ΔSC formed thioester conjugates with the UFM1-specific E2, UFC1, in otherwise wildtype (UFM1 KO ;6xHis-UFM1 ΔSC ) and in double knockout (UFM1 KO , UFSP2 KO ) cells expressing 6xHis-UFM1 ΔSC , but not in double knockout (UFM1 KO , UBA5 KO ) cells expressing 6xHis-UFM1 ΔSC (SI Appendix, Fig.…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…Cell culture: UBA5 -knockout HEK293T cells were used in this study 7 23. Briefly, to generate UBA5 -knockout cells, UBA5 gRNA designed using the CRISPR Design tool (http://crispr.mit.edu/) was subcloned into pX330-U6-Chimeric_BB-CBh-hSpCas9 (Addgene #42230), a human codon-optimised SpCas9 and chimeric gRNA expression plasmid.…”
Section: Methodsmentioning
confidence: 99%
“…Conversely, a search for inhibitors of Ufm1 proteases may identify a compound capable to enriching for ufmylated proteins. A recent report shows that loss of Ufsp2 in cells leads to a dramatic increase in ufmylated targets 16 , suggesting that inhibitors may yield the desired effect. Since heart failure is a leading cause of morbidity and mortality, especially among middle-aged and older adults, this important study reveals ufmylation as a promising pathway to explore for therapeutic benefits in cardiomyopathies, and likely other ER stress-based illnesses.…”
mentioning
confidence: 99%